Relação entre as condições climáticas e a secagem do polvilho azedo e doce de mandioca: um estudo de caso - Domenez, Eduardo Pereira (2022)
Starch is a product of cassava (Manihot esculenta Crantz), being main ingredient of “pão de queijo”, a traditional delicacy of the state of Minas Gerais (Brazil) that has already conquered international market. It can be fermented (sour cassava starch) or not. Traditional cassava starch is dried in the sun, which takes place in the open. Therefore, it is important to know the influence of climatic attributes in that process. The objective of the present work was to study the relationship between those climatic attributes and the physical-chemical and technological parameters of the two types of starches. Two-year data from a starch company in the city of Formiga (MG) were used, crossed with climatic data provided by the National Institute of Meteorology (INMET) at the same time. Correlation between variables (specific volume, pH, titratable acidity, average temperature, thermal amplitude, average relative humidity, radiation and precipitation) were evaluated. Scatter plots were created to observe the lots. In addition, there was a proposal for a regression equation for the specific volume for both starches. The practice of that company in using INMET data for rain forecasting proved to be correct, concentrating the drying of the starch on days favorable to that process. Specific volume of cassava starch didn’t have correlation with the other attributes, demonstrating possibility of establishing a standard without need to know climatic attributes. For sour cassava starch, there was a correlation of the specific volume with the average temperature, radiation, average relative humidity and thermal amplitude, indicating that specific volume is favored with the extension of drying, for carrying out photochemical reactions. It was observed in scatter diagrams that most discrepant lots were obtained mainly by drying done on days of atypical climate, such as rainy days or high radiation. It was not possible to develop an equation of the specific volume as a function of the climatic conditions for cassava starch, showing that the specific volume did not depend on the other variables. Meanwhile, sour cassava starch had pH, titratable acidity, average temperature and radiation as significant variables, with an R2 value of 0.48. Finally, when using the company's internal classification and standard, it was observed that about a third of the sour cassava starch lots were outside that standard, requiring adjustments and greater control of fermentation and drying time.